Understanding early maladaptive schemas formation with traumatic experiences in childhood: a qualitative study - ERDEN ÇINAR, SEVAL (My University, 2023)
This qualitative study offers an in-depth analysis of the traumatic childhood experiences and perception of family relations of individuals in Turkey who have early maladaptive schemas. Criterion sampling yielded 20 individuals after the Young Schema Scale Short Form-3 was administered to 450 young adults to identify those with the most intense and active early maladaptive schemas. Interviews were conducted with participants using questions created by the researchers and analyzed by Interpretative Phenomenological Analysis. The analysis revealed two main themes: conflicting family relationships and lack of marital satisfaction, and dysfunctional parenting. The first theme had three subthemes: conflict and lovelessness between spouse, violent relationships, and relationships open to the negative effect of relatives. The second theme had subthemes about the father and mother. The emerging themes related to fathers include headlines of authoritarian father, ambiguous loss, absence of father, having a traumatic life, dysfunctional parenting and early finished childhood; the themes about their mothers are listed as passive, having traumatic life, dysfunctional parenting and early finished childhood. This study provides detailed information about schemas formation, the experiences and family structures of individuals with high negative schemas which are important for clinical assessment, conceptualization and intervention in counseling and clinical practice.
Keywords: Sağlık Bilimleri; Sosyal ve Beşeri Bilimler; Psikoloji; Klinik Psikolojisi; Sosyoloji; Güvenlik Bilimleri; Ev Ekonomisi; Health Sciences; Social Sciences and Humanities; Psychology; Clinical Psychology; Sociology; Security Sciences; Home Economics; PSİKOLOJİ, KLİNİK; Temel Bilimler (SCI); KRİMİNOLOJİ VE PENOLOJİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); AİLE ÇALIŞMALARI; Psikiyatri; Klinik Tıp (MED); PSYCHOLOGY, CLINICAL; PSYCHOLOGY; Natural Sciences (SCI); CRIMINOLOGY & PENOLOGY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); FAMILY STUDIES; PSYCHIATRY; Clinical Medicine (MED); Genel Sosyal Bilimler; Genel Psikoloji; Psikoloji (çeşitli); Klinik Psikoloji; Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; General Psychology; Psychology (miscellaneous); Psychiatric Mental Health; Psychiatry and Mental Health; Social Sciences & Humanities; Schema therapy; early experiences; interpretative phenomenology; maladaptive schemas; childhood trauma; FATHERS; YOUNG; VULNERABILITY; INVOLVEMENT; DEPRESSION; CONFLICT